(untitled) (Performance, Religion, and Spirituality, 2017)
This article examines the relationship between theology, belief and speech acts. Translated onto or directly performed on digital platforms, speech acts influence the spatial arrangement of protest, especially when such protest concerns theology and belief. Digital platforms such as Facebook and online blogs provide protestors the medium to disseminate and proliferate their ideology, on both the right and the left of the political spectrum. Drawing from the theoretical perspectives of Giorgio Agamben and Shoshana Felman, this study discusses how a network of Christian churches or church affiliated groups and individuals use the internet to counter-perform and protest against the LGBTQ community in Singapore. When such groups theatricalise their objections to any mass assembly of the LGBTQ community and their supporters, the uneasy relationship between theology, state governance, and society plays out in contested ways through offline and online assemblies. Observing the recent 2016 US presidential election and the dissemination of conservative ideology online, the Singapore case study shows a connection between the Christian theology underpinning US politics and the spread of these ideas across the Pacific Ocean through online gestures, tweets, web articles, and digital videos.